ONLINE SHOPPING INDONESIA: CUSTOMER PERCEPTION - Muhsin N. Bailusy; Irfandi Buamonabot; Johan Fahri; Muhammad Asril Arilaha (AIBPM Publisher, 2022)
Online shopping has made changes in consumer behavior when shopping, especially in Indonesia, where online shopping continues to increase. For this reason, the question that arises then is how consumer perceptions are related to online shopping in Indonesia. The purpose of this study is to provide an overview of consumer perceptions of online shopping in Indonesia, namely Tokopedia, Shopee, Bukalapak and Lazada. A total of 850 respondents throughout Indonesia were involved in this study. Consumer perceptions related to online shopping in this study are security, self-efficacy, usefulness, ease of use, quality of e-service (reliability, web design, trustworthiness, personalization and responsiveness), purchase intention and customer satisfaction. The distribution of the questionnaires was carried out using two methods, namely surveys and filling out via google forms which were then analyzed and analyzed using a descriptive statistical approach. The results show that consumers tend to agree regarding security, ease of use, self-efficacy, usefulness, quality of e-service, purchase intention and customer satisfaction. Only consumer perceptions have differences in views related to online and offline buying and selling. In addition, online transactions and privacy of individual data are still a concern for consumers. Finally, some limitations and suggestions for future research are also discussed in this study.